2015
DOI: 10.1080/19443994.2013.874959
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and modeling of column operations on reactive dye removal onto alkaline-treated biomass fly ash

Abstract: A B S T R A C TThe adsorption characteristics of Reactive Black 5 (RB5) dye on alkaline-treated biomass fly ash (TFA) were investigated in aqueous solutions in a fixed-bed column. The breakthrough curves increased with decreasing initial dye concentration and the flow rate, and with increasing bed depth. In this column study, the optimum flow rate and bed depth were 5 ml min −1 and 10 cm, respectively. The Thomas model provided a good prediction of the breakthrough curve of RB5 removal by the TFA. The maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…And adsorption is one of the most commonly used methods because of its simplicity, effectiveness, ease of operation, and reusability. 8,9 A large number of adsorbents, such as clays, 10 metal oxides, 11 activated carbon, 7 and fly ash 12 have been applied to remove dyes from wastewater. However, owing to the high cost and the difficulties related to disposal and regeneration, most of these adsorbents cannot be widely used.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And adsorption is one of the most commonly used methods because of its simplicity, effectiveness, ease of operation, and reusability. 8,9 A large number of adsorbents, such as clays, 10 metal oxides, 11 activated carbon, 7 and fly ash 12 have been applied to remove dyes from wastewater. However, owing to the high cost and the difficulties related to disposal and regeneration, most of these adsorbents cannot be widely used.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A large number of adsorbents, such as clays, metal oxides, activated carbon, and fly ash have been applied to remove dyes from wastewater. However, owing to the high cost and the difficulties related to disposal and regeneration, most of these adsorbents cannot be widely used.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the ash of agricultural waste and by‐products has been reported to remove heavy metal ions from wastewater (Gupta and Sharma, 2003; Fan et al, 2010; Pengthamkeerati and Satapanajaru 2015). Studies have demonstrated that fly ash derived from organic material may be particularly suited to the removal of heavy metals because of the high proportion of unburned C and Si (15–22% SiO 2 in a hydrated amorphous form like silica gel) (Khalid et al, 2000) present in these materials.…”
mentioning
confidence: 99%
“…Of these limited column studies, most of the investigators found that column sorption capacity severely influenced by column operational parameters including flow rate, bed depth and influent dye concentration. [2] During an investigation on continuous remediation of Reactive Black 5 by alkaline-treated fly ash packed in a packed column, Pengthamkeerati et al [170] observed that column dye removal performance increases with decreasing influent dye concentration, raising bed depth and reducing flow rate. The authors used the Thomas model, which showed a good estimation of the Reactive Black 5 breakthrough curve by fly ash.…”
Section: Parameters Affecting Column Adsorption Of Dyesmentioning
confidence: 99%
“…During an investigation on continuous remediation of Reactive Black 5 by alkaline‐treated fly ash packed in a packed column, Pengthamkeerati et al . observed that column dye removal performance increases with decreasing influent dye concentration, raising bed depth and reducing flow rate.…”
Section: Introductionmentioning
confidence: 99%